2009
DOI: 10.1007/s00421-009-1177-4
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training accelerates exhaustive exercise-induced mitochondrial DNA deletion and apoptosis of left ventricle myocardium in rats

Abstract: Even though exhaustive exercise-induced oxidative stress increases the risk of tissue damage, regular endurance training is widely assumed to improve cardiac function and protects against heart disease. We tested the hypothesis that an endurance training program prevents exhaustive exercise-induced increases in cardiac dysfunction and apoptosis in left ventricle (LV). Thirty-two male Sprague-Dawley rats were randomly divided into four groups: sedentary control (C), trained (T), exhaustively exercised (E), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…A potential explanation for the homogeneous cellular phenotype observed in EX ϩ Band might result from the functional demand imposed by exercise training, favoring the autophagic response and/or death of the most dysfunctional and susceptible cells to injury. This idea, although speculative, is supported by reports showing that endurance exercise training is accompanied by terminal deoxynucleotidyl-dUTP nick end labelingpositive nuclei and activation of apoptotic mediators (Bax, cytochrome c, cleaved caspase-3, and cleaved PARP) in LV cardiomyocytes (18) as well as enhanced abundance of cardiac progenitor cells (21). In addition, cardiac autophagy has been recently associated with exercise training, with some data pointing to its involvement in exercise-induced cardioprotection (4,40).…”
Section: Discussionmentioning
confidence: 56%
“…A potential explanation for the homogeneous cellular phenotype observed in EX ϩ Band might result from the functional demand imposed by exercise training, favoring the autophagic response and/or death of the most dysfunctional and susceptible cells to injury. This idea, although speculative, is supported by reports showing that endurance exercise training is accompanied by terminal deoxynucleotidyl-dUTP nick end labelingpositive nuclei and activation of apoptotic mediators (Bax, cytochrome c, cleaved caspase-3, and cleaved PARP) in LV cardiomyocytes (18) as well as enhanced abundance of cardiac progenitor cells (21). In addition, cardiac autophagy has been recently associated with exercise training, with some data pointing to its involvement in exercise-induced cardioprotection (4,40).…”
Section: Discussionmentioning
confidence: 56%
“…Increase of these isozymes in serum is considered generally supportive of myocardial injury 47 . Huang et al 48 reported that endurance training accelerates exhaustive exercise-induced apoptosis in left ventricles of rats, as a result of exhaustive running tests on a treadmill. In this study, the amount of LD 1 variation after exercise in the CLA group was significantly lower than that of the Pla group.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching cardiomyocyte and increased left ventricular wall stress can trigger death receptor as characterized by the increased expression of Fas protein. 22 High-intensity anaerobic physical exercise causes an increase of end-diastolic pressure due to excessive load and can lead to wall stress, which further stimulate sarcomer replication, fiber elongation, and enlargement of cardiac chamber or eccentric hypertrophy. 13 Acute increase of wall stress may lead to replication of sarcomeres, concentric wall thickening and hypertrophy associated with significant increase of left ventricular mass.…”
Section: Methodsmentioning
confidence: 99%